An integrated framework for collaborative robot-assisted additive manufacturing. (September 2022) - Safeea, Mohammad; Bearee, Richard; Neto, Pedro
Abstract: Additive manufacturing (AM) is revolutionizing industry, allowing to prototype and fabricate custom-made parts with complex geometries rapidly and at an affordable cost. The use of robots to perform AM has great potentials due to its flexibility and ability to produce multi-directional fabrication paths, conducting to the production of parts that are unachievable using conventional 3-axis machines. In this study, it is proposed a novel multitasking collaborative robot-assisted AM framework featuring the system design, integration, generation of collision free robot paths/motion, robot control and filament extrusion control. Closed loop inverse kinematics was implemented to avoid singularities when generating AM paths for redundant robots featuring null space issues. The orientation control of the robot's end-effector (EEF) allows to eliminate the stair-like structures in fabricated parts by applying finishing layers, and by this way improving the appearance of curved surfaces, improving mechanical properties and better supporting loads in certain directions. Experimental tests carried out on 7-axis redundant robot manipulator show the viability of the system proposed.